Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Pegawai di BPJS Kesehatan Kantor Cabang Manado - Prayer Queen Lumintang; Sweetly Mumu; Farly Teneh (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
The purpose of this study was to determine the effect of Transformational Leadership on Employee Performance at the Manado Branch Office of BPJS Kesehatan. The research method used is quantitative data with a population consisting of all employees of the Manado Branch of BPJS Kesehatan, totaling 30 people. Data collection was carried out using a questionnaire which was then processed using SPSS software. The results of the validity and reliability tests showed that all indicators were valid and reliable. Linearity, normality, simple linear regression, and F and t tests were carried out to analyze the data. Normality, linearity, and simple linear regression tests showed that Transformational Leadership had a positive and significant effect on Employee Performance. The coefficient of determination (R²) value of 82.9% indicates that most of the variation in Employee Performance is explained by the Transformational Leadership variable. In conclusion, Transformational Leadership plays an important role in improving Employee Performance in this organization.